2006
DOI: 10.1099/mic.0.28922-0
|View full text |Cite
|
Sign up to set email alerts
|

Implication of (Mn)superoxide dismutase of Enterococcus faecalis in oxidative stress responses and survival inside macrophages

Abstract: The gene encoding the manganese-containing superoxide dismutase (MnSOD) of Enterococcus faecalis was characterized. It is transcribed monocistronically from an upstream promoter identified by rapid amplification of cDNA ends (RACE)-PCR. A sodA mutant was constructed and characterized. Growth of the mutant strain was not significantly different from that of its wild-type counterpart in standing and aerated cultures. However, the mutant was more sensitive towards menadione and hydroperoxide stresses. The respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 45 publications
0
55
1
Order By: Relevance
“…As mentioned above, the metabolism of glycerol via the GlpK pathway leads to the generation of H 2 O 2 , and we demonstrated that transient accumulation of this peroxide occurred during growth of the E. faecalis JH2-2 wild-type strain, leading to a growth inhibition which became even more pronounced in mutants affected in peroxidases (24). Since ⌬sodA mutants are more sensitive to externally added H 2 O 2 (18,30,31), the possibility that the growth on glycerol of the JH2-2 ⌬sodA mutant was affected by the intracellular generation of H 2 O 2 during catabolism of this substrate could not be excluded, and we tested this experimentally. While the wild-type JH2-2 strain grew to a final OD 600 of 3.5, the isogenic ⌬sodA mutant entered stationary phase early after start of growth and reached a final OD 600 of only 0.4 (see Fig.…”
Section: Resultsmentioning
confidence: 85%
“…As mentioned above, the metabolism of glycerol via the GlpK pathway leads to the generation of H 2 O 2 , and we demonstrated that transient accumulation of this peroxide occurred during growth of the E. faecalis JH2-2 wild-type strain, leading to a growth inhibition which became even more pronounced in mutants affected in peroxidases (24). Since ⌬sodA mutants are more sensitive to externally added H 2 O 2 (18,30,31), the possibility that the growth on glycerol of the JH2-2 ⌬sodA mutant was affected by the intracellular generation of H 2 O 2 during catabolism of this substrate could not be excluded, and we tested this experimentally. While the wild-type JH2-2 strain grew to a final OD 600 of 3.5, the isogenic ⌬sodA mutant entered stationary phase early after start of growth and reached a final OD 600 of only 0.4 (see Fig.…”
Section: Resultsmentioning
confidence: 85%
“…4a). In E. faecalis, SOD has been shown to be important in protecting cells from damage under oxidative stress (Verneuil et al, 2006). However, zymographic analysis revealed no obvious change in the level of SOD activity in the Slgt mutant compared with the wild-type strain (data not shown).…”
Section: Phenotypic Characterization Of the Slgt Mutantmentioning
confidence: 79%
“…In contrast to streptococci, E. faecalis contains the heme-dependent catalase KatA, which is activated by heme taken up from the environment (259); its implication for virulence has not yet been investigated. Deletion of E. faecalis sodA attenuated resistance to H 2 O 2 and survival in mouse macrophages (254) and microglia (525). E. faecalis also contains three peroxidases: Npr, AhpCF, and Tpx (248).…”
Section: Oxidative Stress and Virulencementioning
confidence: 99%
“…An alternative strategy to counteract superoxide anion radicals is by the production of high levels of intracellular glutathione (252). Various enzymes that are known to counter oxidative stress, namely, MsrAB, AhpCF, Tpx, Npr, KatA, Sod, and HypR, have been characterized for E. faecalis (94,248,(253)(254)(255).…”
Section: Detoxification Of Ros In Labmentioning
confidence: 99%